ACCOUNTING INFORMATION DISCLOSURE: SINGLE VERSUS MULTIPLE BENCHMARK - Praditha, Riza; Haliah, Haliah; Habbe, Abdul Hamid; Rura, Yohanis; Anwar, Anas Iswanto (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2020)
This study aims to analyze the level of estimation bias made by investors based on the form of disclosure of single and multiple benchmark accounting information. The research design uses an experimental laboratory (between-subject). Respondents in this study used 40 students who had attended capital market schools on the Indonesia Stock Exchange as a representation of novice investors. The results of hypothesis testing indicate that the disclosure of accounting information in the form of multiple benchmarks is better than the form of single benchmark information. This is indicated by the smaller error rate of estimation made by investors in predicting future earnings. Thus, the bias in decision making can be minimized by presenting more comprehensive accounting information using multiple benchmark forms.